واقع التفكير الإستراتيجي لدى القادة في المؤسسات الصغيرة والمتوسطة - غرايسة, حمزة; رزوق, ابتهاج (University of eloued جامعة الوادي, 2018)
تعيشالمؤسسةاليومفيبيئةتتميزبالتعقيدوالغموضوتمربالعديدمنالتغيراتتتسمبالإيقاعالسريع،مماجعلهاتواجهتحدياتكبيرةفرضتعليهالتضمناستمراريتهاونجاحها،حيثظهرمفهومالتفكيرالاستراتيجيكردفعللأغلبهاتهالتغيرات،إذقال "إدوارديبوندونو":أنالتفكيرأهمثروةإنسانية . لكنللأسفيعتقدالكثيرونأنهمأكفاءجدافيممارسةهذاالتفكيرلذلكلايستفيدوامنهذهالملكةإلابشكلضئيلجدا،ممايجعلهملايفكروافيبذلأيمجهودلتنميةكفاءاتهمفيالتفكير...ورغمحاجةالقادةالماسةللتفكيرالاستراتيجيلصناعةمستقبلالمؤسساتالصغيرةوالمتوسطةإلاأنالكثيرمنهملاتتوافرلديهمهارةالتفكيرالاستراتيجيمماقديؤديبزوالالمؤسسة . وهذاماهدفتإليهدراستناإلىتوضيحواقعالتفكيرالاستراتيجيلدىقادةالمؤسساتالصغيرةوالمتوسطةبالتطبيقعلىعينةمنالمؤسساتالصغيرةوالمتوسطةلولايةالواديحيثتناولنافيالفصلالأول :مدخلوعمومياتحولالتفكيرالاستراتيجي،وتناولنافيالفصلالثانيماهيةالقائدوالمؤسساتالصغيرةوالمتوسطة،أماالفصلالثالث: فقدتطرقنافيهإلىالدراسةالميدانيةلواقعالتفكيرالاستراتيجيلدىالقادةفيبعضالمؤسساتالصغيرةوالمتوسطةلولاية –الوادي- وذلكبالاعتمادعلىاستبيانوبإتباعالمنهجالوصفيالتحليلي،وفيالأخيرتوصلناإلىمجموعةمنالنتائج،وعلىضوئهاقدمنابعضالتوصياتوالتيأهمها :علىالمؤسساتلتضمنريادتهاوبقائهافيظلاقتصادالسوقأنيتبنىقادتهاتفكيراستراتيجي . Today , the institution is living in an environment of complexity and ambiguity . It goes through many changes which are characterized by rapid rhythm making it face great challenges imposed on it to ensure , its continuity and success where the concept of strategic thinking emerged as a reponse to all these changes .Edured de Bono said : thinking is the most important human wealth. But unfortunately , many believe that they are very competent in practicing this thinking so they benefit from this faculty very little which makes them don’t think of making any effort to develop their competence in thinking ….. Despite the need of leaders to strategically think about the future industry of small and medium institutions .But many of them don’t have the skill of strategic thinking which many lead to the disappearance of the institution . This is the aim of our study to clarify the reality of the strategic thinking of the leaders of small and medium institutions by applying to a sample of S M I from the state of El-oued . We discussed in the first chapter the introduction and generalities about strategic thinking . In the second chapter :what is the leader ,and small and medium institutions , the third chapter dealt with the field study of the strategic thinking of leaders in small and medium institutions in El -oued , based on the questionnaire and following the descriptive analytical approach .  In the end , we arrived to a set of results , and in the light of this , we made some recommendations
مذكرة ماستر ادارة اعمال
Keywords: التفكير الاستراتيجي ، المؤسسات الصغير والمتوسطة ، القادة; Pensée stratégique, petites et moyennes entreprises, dirigeants